1993
DOI: 10.1128/aem.59.5.1430-1436.1993
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and debittering of a tryptic digest from beta-casein by aminopeptidase N from Lactococcus lactis subsp. cremoris Wg2

Abstract: The mode of action of purified aminopeptidase N from Lactococcus lactis subsp. cremoris Wg2 on a complex peptide mixture of a tryptic digest from bovine 1-casein was analyzed. The oligopeptides produced in the tryptic digest before and after aminopeptidase N treatment were identified by analysis of the N-and C-terminal amino acid sequences and amino acid compositions of the isolated peptides and by on-line liquid chromatography-mass spectrometry. Incubation of purified peptides with aminopeptidase N resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(23 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…casei IFPL 99, which indicates a higher level of debittering activity by IFPL 731, possibly related to the strain's high level of aminopeptidase activity (Requena et al 1993). Tan et al (1993) reported degradation In conclusion, differences in proteolytic abilities of lactobacilli strains tested were detected using goats' milk curd slurries, even though the strains exhibited similar peptide profiles. Given that this model system shares similar characteristics with cheeses, it can be used to screen starter bacteria and non-starter bacteria as adjuncts for cheese making, and also to check what contribution they might make to cheese ripening.…”
Section: (260%)mentioning
confidence: 78%
“…casei IFPL 99, which indicates a higher level of debittering activity by IFPL 731, possibly related to the strain's high level of aminopeptidase activity (Requena et al 1993). Tan et al (1993) reported degradation In conclusion, differences in proteolytic abilities of lactobacilli strains tested were detected using goats' milk curd slurries, even though the strains exhibited similar peptide profiles. Given that this model system shares similar characteristics with cheeses, it can be used to screen starter bacteria and non-starter bacteria as adjuncts for cheese making, and also to check what contribution they might make to cheese ripening.…”
Section: (260%)mentioning
confidence: 78%
“…Lactobacilli showed the highest aminopeptidase activity. As aminopeptidases play an important role in the hydrolysis of bitter peptides and in amino acid liberation (Tan et al. , 1993; Sasaki et al.…”
Section: Discussionmentioning
confidence: 99%
“…The role of aminopeptidases in debittering has been verified by using purifed aminopeptidase enzymes (Minagawa et al . 1989; Tan et al . 1993; Bouchier et al .…”
Section: Introductionmentioning
confidence: 99%